Complete mitochondrial genome of sea cucumber, Holothuria (Stauropora) pervicax (Holothuroidea, Holothuriida, Holothuriidae), from Jeju Island, Korea. Issue 1 (2nd January 2019) - Lee, Taekjun; Shin, Sook
Abstract: Holothuria ( Stauropora ) pervicax was a common, widespread tropical holothuroid. The complete mitogenome of H. ( S. ) pervicax was 15, 790 bp in length and consisted of 13 PCGs, 22 tRNAs, and two rRNAs. The gene order and genetic characteristics were same with other mitogenomes of Holothuria . The phylogenetic tree revealed that clade of Holothuria was clearly monophyletic, included H. ( S. ) pervicax .